2020
DOI: 10.3390/ijerph17186912
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks and Potential Sources of Contamination of Groundwater Used by Public Schools in Vhuronga 1, Limpopo Province, South Africa

Abstract: Public schools in most rural areas of South Africa depend on untreated groundwater due to unreliable water supply by the municipalities. This has the potential to cause water-related health problems to school children. Temperature, pH, and electrical conductivity (EC) were measured in situ. Chemical (fluoride, chloride, sulphate, phosphate, nitrate, magnesium, calcium, sodium, and potassium) and microbial (Escherichia coliform (E. coli), Salmonella typhimurium, and Shigella flexneri) water quality parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…It was also seen that the cup/jug (metal, glass, or plastic) used to retrieve the water from the storage vessel was often kept uncovered near the storage vessel and thus exposed to dust, flies, and unwashed hands, similar to the results of other studies in South Africa [ 3 ]. Other potential sources of groundwater contamination could be from agricultural activities and pit latrines [ 51 ] and a few studies have shown that the material of the containers could assist in the survival and transmission of potential pathogenic microorganisms [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also seen that the cup/jug (metal, glass, or plastic) used to retrieve the water from the storage vessel was often kept uncovered near the storage vessel and thus exposed to dust, flies, and unwashed hands, similar to the results of other studies in South Africa [ 3 ]. Other potential sources of groundwater contamination could be from agricultural activities and pit latrines [ 51 ] and a few studies have shown that the material of the containers could assist in the survival and transmission of potential pathogenic microorganisms [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…pseudomallei is ubiquitously distributed in soil and surface water throughout the tropics, including in Asia, the Pacific Islands, sub-Saharan Africa, and Latin America, where boreholes are the most common water supply in the rural areas (1,6,7). In addition to other waterborne infections (7), untreated water supplies have been implicated in previous human B. pseudomallei infections (8-10). B. pseudomallei also was isolated from the compacted earth floor under the bathing tub of a woman who died from septicemic melioidosis in Brazil (11).…”
Section: Discussionmentioning
confidence: 99%
“…Abundance pattern across samples was observed as follows: GWR12 > GWR14 > GWR15 > GWR16 > GWR19 > GWR17. The lowest level of contamination was observed in GWR17, for which only TC exceeded the allowed values for drinking water Teunis et al, 2004;Odiyo et al, 2020Ahmed et al, 2020Odiyo et al, 2020WHO, (2005 Haas et al ( 2014)…”
Section: Heterotrophic Plate Countmentioning
confidence: 99%